Botswana : Technical Assistance Report-Price Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
A technical assistance (TA) mission was conducted by the International Monetary Fund's (IMF) Regional Technical Assistance Center for Southern Africa (AFS)1 during November 22-26, 2021 to continue assisting Statistics Botswana (SB) with developing the producer price index (PPI). Due to ongoing COVID-19 related travel restrictions, this mission was conducted remotely using Microsoft Teams, WhatsApp, and email. Previous missions to assist with developing price indexes were held in February 2019 and October 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy